2006
DOI: 10.1109/jqe.2006.877295
|View full text |Cite
|
Sign up to set email alerts
|

Optical Bistability in a Traveling-Wave SOA Connected to a DFB Laser Diode: Theory and Experiment

Abstract: Abstract-The behavior of two types of gain-clamped semiconductor optical amplifiers under small-signal optical modulation is analyzed both numerically and experimentally. The small-signal gain as well as the crosstalk is investigated in two different injecting schemes. Dependence on mean input power and signal frequency is studied. The study reveals a strong dependence of the small-signal gain on the direction of the data signal as compared to the pump signal. The biggest difference between both amplifier type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…Previously we reported static bistable operation of a semiconductor optical amplifier (SOA) bidirectionally coupled to a distributed feedback laser diode (DFB-LD) [7]. In addition to that, dynamic simulations showed that the device can also be used as an AOFF, i.e., can be set and reset using optical pulses [8].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previously we reported static bistable operation of a semiconductor optical amplifier (SOA) bidirectionally coupled to a distributed feedback laser diode (DFB-LD) [7]. In addition to that, dynamic simulations showed that the device can also be used as an AOFF, i.e., can be set and reset using optical pulses [8].…”
Section: Introductionmentioning
confidence: 93%
“…When a continuous-wave (CW) beam is injected at the SOA side, it has been shown that bistable operation can occur with the actual state depending on the history of the device [7]. The two stable states are defined as either the state where the laser diode is switched ON or the state where the laser diode is switched OFF.…”
Section: Device Descriptionmentioning
confidence: 99%
“…En [Oos06] se propone interconectar un SOA con un DFB-LD (DFB-Laser Diode). La configuración de [Kim04] es muy similar porque se basa en un SOA/DFB-SOA pero utiliza el SOA sólo como amplificador.…”
Section: Figura 216: Configuración De Un Dispositivo óPtico Multi-esunclassified
“…En la Fig. 2.17 se muestra el esquemático del flip-flop de [Oos06]. Al acoplar un SOA con un DFB-LD son posibles dos estados estables de funcionamiento.…”
Section: Figura 216: Configuración De Un Dispositivo óPtico Multi-esunclassified